Position of Electronic Agreements (E-Contract) in Emaster Online Arisan as Evidence in Civil Procedure Law - Saputra, Ade Rizki; Gunati, Mira; Faisal, Ryan (Jurnal Multidisiplin Madani, 2025)
In the digital era, the internet has significantly transformed various aspects of life, including financial systems and social interactions. One notable change is the shift from traditional face-to-face arisan (a rotating savings and credit association) to online arisan facilitated through social media platforms and electronic banking. This study examines the legal validity of electronic agreements (e-contracts) in online arisan, focusing on the case of Emaster Online Arisan as evidence in civil procedure law, particularly in Decision No. 41/Pdt.G/2021/PN Pwd. The research employs a normative legal approach, analyzing the Indonesian Civil Code, Law No. 11 of 2008 on Electronic Information and Transactions (UU ITE), and relevant case law. The findings indicate that online arisan agreements, even if not formally documented, are legally binding as long as they meet the requirements stipulated in Article 1320 of the Civil Code, which includes the agreement of the parties, legal capacity, a specific object, and a lawful cause. The study concludes that electronic agreements are recognized and protected under Indonesian law, and the court's decision in the Emaster case underscores the principle of pacta sunt servanda, ensuring that parties must fulfill their contractual obligations